A Clinical Case of the Hereditary Transthyretin Amyloidosis - E. V. Reznik; T. L. Nguyen; S. V. Borisovskaya; L. V. Brylev; A. V. Zhelnin; N. E. Seksyaev (Архивъ внутренней медицины)
Introduction: Transthyretin (ATTR) amyloidosis is a severe rare disease with wide range of characters without specific symptoms including the damage to the peripheral nervous system and cardiac involvement. Case report: A 60-year-old female patient represented with weakness and paresthesia in the distal parts of the lower limbs, impeding walking for 2 years. Initially, symptoms were considered as a manifestation of degenerative stenosis of the lumbar spine, decompressive laminectomy was performed but the symptoms after surgical treatment persisted. Based on data from clinical and electroneuromyographic examinations, axonal sensorimotor polyneuropathy was diagnosed. Genetic testing of the patient, her elder sister, son and daughter using the Sanger sequencing method detected a variant of the nucleotide sequence in the fourth exon of the transthyretin gene (Chr18: 29178562, rs148538950, NM_000371.3: c.G368A: p. Arg123His) in the heterozygous state. A subcutaneous fatty tissue biopsy of abdominal wall with a Congo red stain and polarized light examination revealed amyloid microdeposits, grade CR 1+ (minimal deposits), confirmed the diagnosis of familial ATTR-amyloidosis. Echocardiography revealed concentric left ventricular wall thickening with normal end diastolic size and volume, preserved ejection fraction, left atrial enlargement, pulmonary hypertension and type 1 diastolic dysfunction. Specific anti-amyloid therapy — tafamidis was prescribed. Conclusion: In patients with peripheral polyneuropathy and left ventricular hypertrophy of unknown etiology, a complex examination is necessary for the timely detection and treatment of amyloid polyneuropathy and cardiomyopathy.